2020
DOI: 10.3390/nano10091891
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the ZnTiO3/TiO2 Nanocomposite Supported in Ecuadorian Clays for the Adsorption and Photocatalytic Removal of Methylene Blue Dye

Abstract: Currently, the study of semiconductor materials is very promising for the photocatalytic remediation of hazardous organic substances present in the air and water. Various semiconductors have been investigated in this interesting photo-assisted methodology, among them metal oxides such as ZnO, TiO2 and their derivatives. In this study, ZnTiO3/TiO2 was synthesized by the sol-gel method using Ti(OC3H7)4 and Zn(CH3COO)2 · 2H2O as reagents. The role of several conditions such as synthesis temperature and TiO2:ZnO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 75 publications
4
19
1
Order By: Relevance
“…Regarding the results, the diffraction pattern showed that R-Clay was formed from kaolinite (K), quartz (Q), and hematite (H), while G-Clay consisted mainly of metahalloysite (M) and quartz (Q). Furthermore, Figure 1 shows the diffraction pattern of the ZnTiO 3 /TiO 2 heterostructure, which was obtained without impurities, as we reported in previous works [ 26 ].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Regarding the results, the diffraction pattern showed that R-Clay was formed from kaolinite (K), quartz (Q), and hematite (H), while G-Clay consisted mainly of metahalloysite (M) and quartz (Q). Furthermore, Figure 1 shows the diffraction pattern of the ZnTiO 3 /TiO 2 heterostructure, which was obtained without impurities, as we reported in previous works [ 26 ].…”
Section: Discussionmentioning
confidence: 73%
“…Table 6 shows that the presence of the mixed oxide ZnTiO 3 /TiO 2 did not significantly improve the MB adsorption capacity of the extrudates compared to the extrudates free of ZnTiO 3 /TiO 2 . However, this mixed oxide can act as a photocatalyst to improve MB removal in aqueous systems when the process is carried out under UV or solar light, as we reported in a previous study [ 26 ]. The efficiency of ZnTiO 3 /TiO 2 in the photocatalytic removal of MB in aqueous systems depends on the appropriate contact between the photocatalyst and the dye.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations